2001
DOI: 10.1016/s0370-2693(01)00832-2
|View full text |Cite
|
Sign up to set email alerts
|

Secondary electrons and positrons in near earth orbit

Abstract: The secondary e + and e − populations in near earth's orbit have been calculated by simulation. The results are in very good agreement with the recent AMS measurements. The e + over e − flux ratio for particles below the geomagnetic cutoff appears to be due to the geomagnetic East-West effect.The study of particle populations in the earth environment has been a field of intense research activity for more than 50 years [1]. After a period of latence, the field is regaining interest with the new generation of am… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 25 publications
1
25
0
Order By: Relevance
“…After the AMS data had become available, many physicists [62][63][64][65][66][67] have made detailed Monte Carlo simulations of the second spectrum phenomenon by means of several independent methods. The methods included the primary proton and helium nucleon interactions in the atmosphere with tracing all trajectories in the Earth's magnetic ÿeld.…”
Section: Simulation Analysis Of the Second Spectrummentioning
confidence: 99%
“…After the AMS data had become available, many physicists [62][63][64][65][66][67] have made detailed Monte Carlo simulations of the second spectrum phenomenon by means of several independent methods. The methods included the primary proton and helium nucleon interactions in the atmosphere with tracing all trajectories in the Earth's magnetic ÿeld.…”
Section: Simulation Analysis Of the Second Spectrummentioning
confidence: 99%
“…Results for albedo and quasitrapped particles are in agreement with AMS-01 data. Calculations in paper [4,3] shows that well-known East -West effect leads…”
Section: Resultsmentioning
confidence: 99%
“…More modern Monte-Carlo simulation also were undertaken to explain results of AMS-01 experiments [2], e.g. [4,3]. It was shown that well-known East -West effect leads to positron excess in near equatorial region for quasitrapped and trapped components from this source.…”
Section: Introductionmentioning
confidence: 99%
“…A positron excess is therefore observed. Simulations performed in the work of Derome et al [2001], Plyaskin [2008], and Lipari [2002] elucidated the nature of particle propagation in near‐Earth space and included important effects due to the East‐West asymmetry of the geomagnetic cutoff. Gusev et al [1985] discuss this effect in more detail.…”
Section: Introductionmentioning
confidence: 99%